Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3346/jkms.2016.31.6.852
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Blood Lead Concentration in Korea: Study Using the Korea National Health and Nutrition Examination Survey (2008–2013)

Abstract: Physical activity normally has a positive influence on health, however it can be detrimental in the presence of air pollution. Lead, a heavy metal with established adverse health effects, is a major air pollutant. We evaluated the correlation between blood lead concentration and physical activity using data collected from the Korea National Health and Nutrition Examination Survey. Multivariate logistic regression analysis was performed after dividing participants according to whether they were in the top 25% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In this way, an increase could be possible in toxic metals ingested [18]. Previous studies have reported a high probability of sportsmen presenting higher serum concentrations of Pb than sedentary individuals, because of pollution [31]. In relation to time effect, the ANOVA showed significant differences in Pb (p < 0.05), similar to those previously obtained [32].…”
Section: Discussionsupporting
confidence: 86%
“…In this way, an increase could be possible in toxic metals ingested [18]. Previous studies have reported a high probability of sportsmen presenting higher serum concentrations of Pb than sedentary individuals, because of pollution [31]. In relation to time effect, the ANOVA showed significant differences in Pb (p < 0.05), similar to those previously obtained [32].…”
Section: Discussionsupporting
confidence: 86%
“…The significantly high blood level of Cd in females than in males was observed beginning in the 30s. Human exposure to Pb could be affected by individual outdoor physical activities in school-aged subjects and individual behaviors including smoking habits and occupation 2039. Blood Hg level in the general population could be affected by individual lifestyle aspects like smoking and alcoholic drinking, and by diet, especially seafood consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Human exposure to Pb could be affected by individual outdoor physical activities in school-aged subjects and individual behaviors including smoking habits and occupation. 20 39 Blood Hg level in the general population could be affected by individual lifestyle aspects like smoking and alcoholic drinking, and by diet, especially seafood consumption. The latter could vary in Korea depending on whether a person lived near the coast or inland.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-individual variation in blood Pb level is affected by various lifestyle and behavioral factors (i.e., smoking, drinking, dietary intake, and physical activity), as well as exposure dose [ 7 , 9 , 12 14 ]. In addition, genetic differences related to Pb toxicokinetics and toxicodynamics influence the body burden and toxic effects of this metal [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%